2018
DOI: 10.1007/978-3-319-91287-5_21
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Prefrontal Cortex Oxygenation Levels During Cycling in the Supine and Upright Positions

Abstract: The purpose of this study was to compare the prefrontal cortex (PFC) oxyhaemoglobin (HbO) levels observed during cycling in the upright and supine positions. Twelve healthy volunteers were randomly assigned to either the upright or supine position. After measuring maximal oxygen consumption (VOmax) with a cycle ergometer in the upright position, each subject exercised at an intensity corresponding to 50% of the VOmax for 20 min. HbO levels in the right PFC (R-PFC) and left PFC (L-PFC) were measured using near-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Previous studies have demonstrated that fNIRS is an appropriate and reliable method for measuring neurovascular coupling in adults during both simple motor tasks (see Leff et al 2011) as well as complex body movements such as walking/running (Harada et al 2009; Holtzer et al 2011; Suzuki et al 2004), rowing (Nielsen et al 1999), squatting (Kenville et al 2017), juggling (Carius et al 2016) or playing table tennis (Balardin et al 2017). Moreover, cycling on an ergometer has been established in several studies as a standardized and comparable task for measuring brain activation during exercise using fNIRS (Ohyanagi et al 2018; Radel et al 2018; Tempest and Parfitt 2016; Tempest and Reiss 2018). Nevertheless, previous investigations were mainly limited to fNIRS measurements focusing on prefrontal brain regions (Giles et al 2014; Jung et al 2015; Rupp et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that fNIRS is an appropriate and reliable method for measuring neurovascular coupling in adults during both simple motor tasks (see Leff et al 2011) as well as complex body movements such as walking/running (Harada et al 2009; Holtzer et al 2011; Suzuki et al 2004), rowing (Nielsen et al 1999), squatting (Kenville et al 2017), juggling (Carius et al 2016) or playing table tennis (Balardin et al 2017). Moreover, cycling on an ergometer has been established in several studies as a standardized and comparable task for measuring brain activation during exercise using fNIRS (Ohyanagi et al 2018; Radel et al 2018; Tempest and Parfitt 2016; Tempest and Reiss 2018). Nevertheless, previous investigations were mainly limited to fNIRS measurements focusing on prefrontal brain regions (Giles et al 2014; Jung et al 2015; Rupp et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Positioning of the optodes and receivers with the associated inter-optode distances (IODs) varies and is described in Tables 5A , B . Nineteen studies used the international EEG 10-20 system with optode placements over the prefrontal lobe at Fp1,Fp2, Fp3, and/or Fp4 position ( Rupp and Perrey, 2008 ; Timinkul et al, 2008 ; Billaut et al, 2010 ; Keramidas et al, 2011 ; Rupp et al, 2013 ; Giles et al, 2014 ; Oussaidene et al, 2015 ; Santos-Concejero et al, 2015 , 2017 ; Pires et al, 2016 ; Tempest and Parfitt, 2016 ; Tsubaki et al, 2016 , 2018 , 2020 ; Takehara et al, 2017 ; Tempest et al, 2017 ; Asahara and Matsukawa, 2018 ; Ohyanagi et al, 2018 ; Stevens et al, 2018 ) pecifying this location as ± 3 cm from the midline, just above the supra-orbital ridge ( Bhambhani et al, 2007 ; Miyazawa et al, 2013 ). Jung et al (2015) used Broadman area 10, Montreal Neurophysiological Institute (MNI) coordinates [( x / y / z ) −40, 50, 0], two studies performed a three-dimensional T1-weighted MRI scan, marking the optode location for the left and right PFC ( Suzuki et al, 2004 ; Fumoto et al, 2010 ), and finally, two studies placed the device on the participants’ forehead without specifying the exact location of the optode placement ( Shibuya et al, 2004 ; Kounalakis and Geladas, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies measured TTE, TT, a constant load with fixed intensity- and adaptive walking/running-exercise protocols. Eleven of the included studies assessed PFC oxygenation during whole-body endurance protocols with a constant intensity and fixed duration ( Ide et al, 1999 ; Fumoto et al, 2010 ; Miyazawa et al, 2013 ; Rupp et al, 2013 ; Giles et al, 2014 ; Tsubaki et al, 2016 , 2018 ; Radel et al, 2017 ; Takehara et al, 2017 ; Hiura et al, 2018 ; Ohyanagi et al, 2018 ). In these studies, participants were asked to complete an endurance cycling task at a certain predetermined intensity (e.g., %HRmax and %VO 2p eak ) for a predetermined time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the drawbacks of EEG and the advantages of fNIRS, fNIRS is currently better suited for measurements of changes in cortical brain activity during physical exercises in unconstrained environments [ 50 , 102 , 103 ]. In fact, fNIRS has been applied during a variety of physical exercises such as juggling [ 104 ], balancing [ 105 , 106 , 107 , 108 , 109 , 110 ], walking (for review see [ 111 , 112 ]), resistance exercises [ 113 , 114 , 115 , 116 ], dancing [ 117 , 118 , 119 ], tai chi [ 120 , 121 ], climbing [ 122 ], synchronized swimming routines [ 123 ], table tennis [ 124 ], running [ 125 , 126 , 127 ], and predominantly during cycling [ 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ,…”
Section: Which Portable Neuroimaging Tools Can Be Used To Assess Bmentioning
confidence: 99%